DETERMINATION OF THE DOSE OF PROCESSING GRAIN RAW MATERIALS WITH OZONE-AIR MIXTURE DURING VIBRATION DRYING - PRYSIAZHNIUK, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Increasing grain production and the preparation of the required amount of seed place new demands on the machinery and technology used for post-harvest treatment and, in particular, the drying of crops. As classical thermal methods of grain drying are very energy-intensive, the possibility of their effective application is limited by the properties of the dried material. The dryers used are physically and morally obsolete and do not meet modern energy saving requirements. Therefore, it is necessary to carry out intensive steps to develop and implement in the production of modern high-performance methods of grain drying and drying equipment designs. Promising ways to improve the quality of grain material and reduce energy consumption in the technological operation of drying is the use of vibration, ensuring uniform processing of grain material by constantly updating the surface of the grain in contact with the drying agent and the introduction of ozone drying. To implement high-quality drying of grain raw materials, an experimental model of a vibro-ozone complex was designed and manufactured, in which the processed material is subjected to vibration, which increases and renews the heat transfer surface. As a result, there is an intensive removal of moisture, increasing the drying rate. The drying process is moderate throughout the layer, without causing local overheating of the material. When drying grain raw materials in the vibro-ozone complex, in order to optimize the implementation of this technological process, it is necessary to establish one of the important parameters, namely the dose of treatment with ozone-air mixture. The method of determining the dose of processing of grain raw materials during drying with ozone-air mixture using the developed vibro-ozone complex, providing high-quality implementation of the technological process while reducing energy consumption.